2021
DOI: 10.3389/fphy.2021.731941
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of Nematode Connectomes Based on Network Dimension-reduced Method

Abstract: The whole map of nematode connectomes provides important structural data for exploring the behavioral mechanism of nematodes, but to further reveal the functional importance and resilience pattern of nematode neurons, it is necessary to effectively couple the regulatory relationship between neurons and their topology. Here, with a typical signal excitation function we propose a model to capture the interacting relationship between the neurons, because a differential equation depicts the activity of a neuron, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…( 2018 ) then performed an effective 2D dimension reduction using the degrees and eigenvector respectively as weights and showed that weighted averaging during the dimension reduction process is necessary due to the lack of sufficient randomness in the real network structure. At present, dimension reduction has been widely applied to various complex systems (Dongli et al., 2021 ; Laurence et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…( 2018 ) then performed an effective 2D dimension reduction using the degrees and eigenvector respectively as weights and showed that weighted averaging during the dimension reduction process is necessary due to the lack of sufficient randomness in the real network structure. At present, dimension reduction has been widely applied to various complex systems (Dongli et al., 2021 ; Laurence et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%